2021
DOI: 10.1007/s42452-021-04186-3
|View full text |Cite
|
Sign up to set email alerts
|

In-situ carbonization of ZIF-67 to fabricate magnetically Co/N-mC with high adsorption capacity toward water remediation

Abstract: Co and N co-modified mesoporous carbon composites (Co/N-mC) have been simply prepared at low cost from the carbonization of ZIF-67 wherein not only providing surface N-modification for promoting the adsorption behavior of acidic dyes, but also constructing a magnetic property for convenient separation. Co/N-mC composite presented the adsorption ability of MO (178 mg g−1) > RhB (141 mg g−1) (T = 25 °C, pH = 7.0, C0 = 20 mg L−1) because of its spacious porous structure (BET: 250.8 m2 g−1; pore size: 3.9 nm) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The ZIF-67 showed a very high surface area of 1402 m 2 g −1 when compared with other results found in the literature. 21,22 It was observed that the surface area of the catalyst increased remarkably with an increase in the pyrolysis temperature. The obtained surface area values were 290, 410, 471, and 530 m 2 g −1 for the post-carbonization of AL-Co/NGC-T, with T increasing from 600 °C to 900 °C as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ZIF-67 showed a very high surface area of 1402 m 2 g −1 when compared with other results found in the literature. 21,22 It was observed that the surface area of the catalyst increased remarkably with an increase in the pyrolysis temperature. The obtained surface area values were 290, 410, 471, and 530 m 2 g −1 for the post-carbonization of AL-Co/NGC-T, with T increasing from 600 °C to 900 °C as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5a) revealed a pure sodalite crystal structure with sharp peaks, which were are well indexed, and matches with previously reported spectra found in the literature. 21,22 The characteristic peaks of ZIF-67 changed due to the effect of thermal pyrolysis, revealing a new set of peaks corresponding to carbon and metallic Co as shown in Fig. 5a and b.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…To create magnetic carbon-based nanocomposites, [10][11][12] a promising strategy seems to be the preparation, first, of a single mixture of the initial polymer and magnetic precursors. Further transformation of the obtained compounds into final magnetic carbon-based composites using the technology of high-temperature pyrolysis in an inert atmosphere allows [13][14][15] to suitably decorate carbon materials with various magnetic nanoparticles (NPs), i. e. ex situ.…”
Section: Introductionmentioning
confidence: 99%